2019
DOI: 10.1002/joc.6435
|View full text |Cite
|
Sign up to set email alerts
|

Projected spatial patterns in precipitation and air temperature for China's northwest region derived from high‐resolution regional climate models

Abstract: Derived from realistic global warming scenarios, long‐term projections of spatial patterns in precipitation and temperature in hydrology and climatology can serve to evaluate climate risk, explore sources of renewable energies and allow local‐scale data to inform decisions regarding agricultural, ecosystem, social, recreational and economic activities. Under the CORDEX‐EA project, the precipitation and temperature projections (2020–2045) for the economically and socially important region of Northwestern China … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 106 publications
1
2
0
Order By: Relevance
“…These extreme conditions have the potential to increase flash floods and runoff (Roudier et al., 2014), reduce soil moisture (Diedhiou et al., 2018; Koné et al., 2020), and increase the risk of agricultural droughts (Mechiche‐Alami & Abdi, 2020). However, it has to be mentioned that the bias‐correction has the potential to alter the projected patterns of extreme precipitation and temperature; this is not limited to this study or region but has been shown for other works (e.g., Adeyeri et al., 2020; Guo et al., 2018; Yin et al., 2020). The projected declines in precipitation and increases in temperature in Western Africa contribute to the decline in surface and groundwater availability and accessibility, affect the agriculture and hydrology sectors.…”
Section: Future Climate Change Signalsupporting
confidence: 55%
“…These extreme conditions have the potential to increase flash floods and runoff (Roudier et al., 2014), reduce soil moisture (Diedhiou et al., 2018; Koné et al., 2020), and increase the risk of agricultural droughts (Mechiche‐Alami & Abdi, 2020). However, it has to be mentioned that the bias‐correction has the potential to alter the projected patterns of extreme precipitation and temperature; this is not limited to this study or region but has been shown for other works (e.g., Adeyeri et al., 2020; Guo et al., 2018; Yin et al., 2020). The projected declines in precipitation and increases in temperature in Western Africa contribute to the decline in surface and groundwater availability and accessibility, affect the agriculture and hydrology sectors.…”
Section: Future Climate Change Signalsupporting
confidence: 55%
“…For the whole of Northwest China, both annual precipitation and annual average temperature are projected to increase under different emissions scenarios. Among them, the highest value of precipitation increase appears in high-elevation mountainous areas, but the highest value of temperature increase appears in low-elevation oases and deserts [40,41]. According to the analysis results of the CMIP6 ensemble modeling, annual precipitation in most arid regions of Central Asia, especially in Tianshan Mountains Ecozone and Northern Central Asia, increases significantly with the increase of temperature.…”
Section: Persistence Of the Warming And Wetting Trend And Socioeconomic Implicationsmentioning
confidence: 99%
“…The bias in the data could be related to the mean, SD , temporal distribution, frequencies, and the nature of extreme occurrences (Leander and Buishand, 2007). Several BC methods are available that vary in applicability and limitations and are discussed extensively in the climate impact studies (Ehret et al ., 2012; Teutschbein and Seibert, 2012; Chen et al ., 2013; Rajczak et al ., 2016; Rohith and Jayakumar, 2017; Turco et al ., 2017; Yin et al ., 2020).…”
Section: Introductionmentioning
confidence: 99%